Resultados a curto prazo do Bypass Gástrico vs Sleeve Gástrico na Super Obesidade: análise num único centro - Carolina Coelho Pais Neto (2021)
Background: Super obesity (BMI ≥ 50 kg/m2) is associated with substantial morbidity and mortality. While the most common bariatric procedures are well stablished in milder forms of the disease, patients with super obesity remain a unique challenge as they present greater operative risk and produce sub-optimal results after surgical treatment. Our aim was to assess the effectiveness and safety of laparoscopic Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) in the super obese population. Methods: We performed a retrospective observational study of 46 patients with super obesity submitted to RYGB (n=19) or SG (n=27) in 2019 at a specialized high-volume center. The primary endpoint was to assess weight loss and comorbidities resolution at 6- and 12-months follow-up. Secondarily, postoperative complications were also evaluated. Results: In the first year after surgery, weight loss was tendentially higher in the RYGB group. The %EWL at 12 months was 70.74% after SG and 77.27% after RYGB (p = 0.154) and the %TWL was 37.87% and 41.49%, respectively (p = 0.089). Successful rates of weight loss were achieved in almost all patients, with no significant differences between SG and RYGB, both %EWL ≥ 50% and %TWL ≥ 20%. Remission and improvement rates of obesity-related comorbidities were comparable between SG and RYGB (66.7% vs 62.5% in Diabetes, 66.7% vs 70.0% in Hypertension, 57.1% vs 55.6% in Dyslipidemia and 37.5% vs 50.0% in Obstructive Sleep Apnea, at 12 months follow-up, respectively). Operative time was lower for SG (p<0.001) and one perioperative complication was observed in the RYGB group. Postoperative complications were the same for both groups (one in each), with one patient in the RYGB group requiring readmission and reintervention. Conclusion: In our study population, SG and RYGB seem to be effective and safe procedures for patients with super obesity. RYGB had a tendency for improved weight loss in the first year.